Saidiya Hartman i krnąbrne biografie. Co czarne herstorie mogą zrobić dla polskiego „zwrotu ludowego”? - Łukasz Kiełpiński (Adeptus, 2021)
Saidiya Hartman and Wayward Biographies: What Can Black Herstories Do for the Polish “People’s Turn”?